Intra-guild spatial niche overlap among three small falcon species in an area of recent sympatry. Issue 1 (31st December 2022) - Berlusconi, A.; Preatoni, D.; Assandri, G.; Bisi, F.; Brambilla, M.; Cecere, J. G.; Cioccarelli, S.; Grattini, N.; Gustin, M.; Martinoli, A.; Rubolini, D.; Sbrilli, A.; et al.
Abstract: Climate warming and land-use change are reshuffling the distribution of wild organisms on a global scale. Some species may expand their ranges and colonize new regions, which may greatly affect ecological interactions among pre-existing species and colonizers. In the last decades, such processes have originated a unique condition of sympatry among three Eurasian small Falco species (common kestrel F. tinnunculus, lesser kestrel F. naumanni, red-footed falcon F. vespertinus ) in the intensively cultivated farmland habitats of the Po Plain (Northern Italy). This provides an excellent opportunity to investigate patterns of spatial niche overlap during the initial phases of the establishment of sympatry. To investigate spatial niche overlap of the three falcon species, we relied on Environmental Niche Models (ENMs) based on widespread breeding occurrence data obtained through field surveys and citizen science programs (during the 2018–2020 period). ENMs were based on bioclimatic and land-use variables in an ensemble modelling framework. We estimated species-specific relative contributions of each climatic and land-use variable and its response curves effect. Eventually, we generated spatial correlation maps of the potential species' distributions to derive spatially-explicit predictions of potential co-occurrence areas among the three species. Overall, eco-climatic determinants of the distribution of lesser kestrel and red-footed falcon were similar, resulting in a strong association with intensive arable lands and dry continental climate. Consistently, we found a high spatial correlation between the suitability maps of the two species, with highly suitable areas located in the Central-Eastern area of the Po Plain, corresponding to the core range of both species. Conversely, the common kestrel emerged as a habitat generalist and was widely distributed throughout the Po Plain. Our findings suggest that the recent sympatry between lesser kestrels and red-footed falcons in the Po Plain may promote ecological interactions and intra-guild competition.